2014
DOI: 10.1021/nn5026912
|View full text |Cite
|
Sign up to set email alerts
|

Selective Assembly of DNA-Conjugated Single-Walled Carbon Nanotubes from the Vascular Secretome

Abstract: Colloidal dispersion of single-walled carbon nanotubes (SWCNTs) is often the first processing step to many of their unique applications. However, dispersed SWCNTs often exist in kinetically trapped states where aggregation can be of concern. Recent work revealed prominent DNA–SWCNT aggregation following intravascular injection. In this study, we performed detailed analysis of DNA–SWCNT aggregate formation, structure, and composition in the context of endothelial cell condition media. Interestingly, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…It is also important to highlight the caveat that DNA‐SWCNT has the potential to form transient interparticle associations . During SPT experiments, it was observed that these associations can form with time and can be avoided through preexperiment agitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to highlight the caveat that DNA‐SWCNT has the potential to form transient interparticle associations . During SPT experiments, it was observed that these associations can form with time and can be avoided through preexperiment agitation.…”
Section: Resultsmentioning
confidence: 99%
“…[54] It is also important to highlight the caveat that DNA-SWCNT has the potential to form transient interparticle associations. [55] During SPT experiments, it was observed that these associations can form with time and can be avoided through preexperiment agitation. Due to this effect, as AUC studies require prolonged preparation and experiment, it is conceivable that the resulting hydrodynamic radius is skewed toward higher values.…”
Section: A Combination Of Methodsmentioning
confidence: 99%
“…This discrepancy is likely a result of varying ionic conditions and adsorption of proteins from the tissue, which are known to attenuate SWNT fluorescence intensity. 33,34 Our results demonstrate that SWNT fluorescence wavelength shifts provide a robust optical readout for chemotherapeutic drug imaging in the relevant biological milieu of muscle tissue. 5,35…”
Section: Evaluating Swnt Nanosensors Dox Detectionmentioning
confidence: 77%
“…Surface proteins present on cell membranes with high charge densities have been shown to promote this red-shift upon first contact with DNA-SWCNTs before endocytosis [37]. Additionally, the exposure of DNA-SWCNTs to serum-containing cell culture media can produce aggregation and spectral modulation by protein-DNA electrostatic interactions [39]. We attribute the initial red-shift observed to a combination of these factors directly following a pulse of (GT)n-SWCNTs, in which the macrophages contained both membrane bound particles that had not yet been internalized as well as newly-formed endosomal vesicles that essentially forced DNA-SWCNTs to form small aggregate complexes with other phagocytosed proteins and cargo.…”
Section: Resultsmentioning
confidence: 99%